Determination Method of Reasonable Reinforcement Parameters for Subsea Tunnels Considering Ground Reinforcement and Seepage Effect - Zhenyu Sun; Dingli Zhang; Qian Fang (Applied Sciences, 2019)
The key issue for construction of subsea tunnels through unfavorable geological conditions is to determine a reasonable reinforcement scheme, while the core problem for the reinforcement design is to accurately evaluate the mechanical behavior of surrounding rock with ground reinforcement. Considering that advanced curtain grouting and full-face grouting are widely used in subsea tunnels, a mechanical model for the subsea tunnel surrounding rock accounting for both ground reinforcement and seepage effect was established. According to the distribution and extent of the plastic zone(s), six potential configurations were appropriately analyzed, which were validated by numerical simulations and analytical solutions for simplified settings from the literature. The sensitivities of the reinforcement parameters were examined, and by taking into account the tunnel radial displacement and the seepage quantity as the main objectives, the multi-objective optimization of the reinforcement parameters was put forward via the stratified sequencing method. Finally, application of the proposed method to the Qingdao Jiaozhou bay subsea tunnel project in China was explained. Research results could provide insightful ideas for the quantitative design of the ground reinforcement of subsea tunnels and may have reference value for their construction safety through unfavorable geological conditions.